Menerapkan Nilai Kearifan Lokal Budaya Samin Dalam Pemerintahan di Indonesia - Syahrul Kirom (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2021)
Abstract: The moral crisis hit the mental and character of the Indonesian nation with widespread cases of corruption, lies and dishonesty in all human activities. In fact, Indonesian culture has very good customs and traditions if we want to explore the ethical values of archipelago culture such as the Samin culture in Central Java. This paper was done using qualitative research. The formal object of this research is ethics, while the material object is the local wisdom value of the Samin community. The method used is the historical continuity method and heuristic method. This step was carried out with the aim of drawing into the history of Samin's culture and to be related to the current situation, related to the values of local wisdom of Samin culture. The results of this study conclude, that it turns out that the negative stigma against Samin culture is not good, who is ignorant and disobedient to taxes, does not want formal schooling with the aim of fighting colonialism. 1), the ethical value of honesty in the culture of samin with the slogan biasakno, kuliknano, pangucapmu, in karo karepe atimu means that it must be accustomed to between verbal and heart, that is, the values of honesty in heart and verbally must be the same, and should not lie. 2). In the words of the Samin people, dhuwekmu yo dhuwekku, mulo iku is sincere, it means that what you have is mine, then be sincere, the purpose of this expression is actually to build an act of mutual giving and receiving ours together with the intention of salig please help and be full of sincerity later who repays God. Key Words: Samin, Ethics, Culture, Local wisdom